Analysis Of Students Visual Learning Styles in View Of Learning Outcomes in the Cognitive Domain Of Students - Sulistri, Emi; Mariana, Dewi; Yasin, Robi Nur (Institut Agama Islam Negeri Palopo, 2023)
This study aims: 1) to describe students' visual learning styles in terms of learning outcomes in the cognitive domain of students in science class V students; 2) to describe the factors that influence the visual learning style of fifth grade students. The method used is descriptive qualitative. The subjects in this study were 6 grade V students at SDN 14 Singkawang, consisting of 2 students in the high category, 2 students in the medium category and 2 students in the low category. Data collection techniques in this study are measurement techniques, indirect communication techniques and direct communication techniques. Data analysis techniques using data reduction, data presentation and drawing conclusions. The research results show that students with high cognitive learning outcomes consist of 2 students who have high and low visual learning styles. Students with medium cognitive learning outcomes consist of 2 students who have moderate and high visual learning styles. In addition, students with low cognitive learning outcomes consisted of 2 students who had low and moderate visual learning styles. Factors that influence students' visual learning styles consist of 4; 1) genetic factors, 2) intelligence factors, 3) sensory factors and environmental factors.